Harnessing microbial consortia for induced systemic resistance and sustainable management of dry root rot in cluster bean under hot arid climatic conditions - Singh, Devendra; Verma, Aman; Jadon, Kuldeep Singh; Mahla, Hans Raj; Kakani, Rajesh Kumar (Frontiers in Microbiology, 2025)
Dry root rot, caused by Macrophomina phaseolina, severely threatens cluster bean production, necessitating sustainable management strategies. This study aimed to screen, characterize and evaluate microbial isolates with antagonistic potential against M. phaseolina. Among 763 isolates, Trichoderma breve 37F, Pseudomonas sp. 8B, Aneurinibacillus aneurinilyticus 16B, and Bacillus velezensis 32B exhibited strong biocontrol and plant growth-promoting traits. All four biocontrol agents demonstrated good compatibility. Pot experiments revealed that the four-microbe consortium comprising T. breve 37F + Pseudomonas sp. 8B + A. aneurinilyticus 16B + B. velezensis 32B significantly suppressed M. phaseolina, achieving 87.13% disease control and declining the percent disease incidence (PDI) to 16.7%. This consortium also enhanced plant growth, increasing plant height (1.66-fold), fresh weight (2.81-fold), dry weight (2.56-fold) and yield (21.4-fold) over the infected control. Significant improvements were observed in plant physiological and biochemical attributes, including increased total chlorophyll (3.16-fold), carotenoids (1.95-fold), total phenols (2.11-fold), flavonoids (2.53-fold), antioxidant activity (3.21-fold) and tannins (4.72-fold), alongside a 46.8% reduction in electrolyte leakage. Antioxidant enzyme activities, including peroxidase (4.05-fold), polyphenol oxidase (2.69-fold), phenylalanine ammonia lyase (1.93-fold), tyrosine ammonia lyase (2.01-fold), superoxide dismutase (2.94-fold) and catalase (2.25-fold), were significantly upregulated in consortium-treated plants. Field validation confirmed the efficacy of the four-microbe consortium, reducing PDI to 40.0% (42.0% disease control) while enhancing seed yield by 2.79-fold and 1.67-fold over the infected and mock controls, respectively. These findings demonstrate the potential of a microbial consortium as an eco-friendly biocontrol strategy. Future work should focus on formulation and large-scale field validation.